Neurological findings spectrum in Celiac disease - Aksoy, Erhan; Tıraş-Teber, Serap; Kansu, Aydan; Deda, Gülhis; Kartal, Ayşe (The Turkish Journal of Pediatrics, 2016)
We aimed to provide early diagnosis by determining possible Celiac disease related subclinical or symptomatic neurological abnormalities in children in order to decrease risk of mortality and morbidity. Children with Celiac disease were assessed with neurological examination, neurophysiological tests and neuroimaging. A total of 65 patients were included in the study. The neurological examination was abnormal in 4 patients. There were EEG abnormalities in 5 patients, VEP was abnormal in 7 patients, BAER was abnormal in 1 patient, ENMG was abnormal in 8 patients, and there were abnormal findings on neuroimaging in 2 patients. The Celiac disease related neurological complications that manifest in adulthood usually lay their foundations in childhood. Therefore, it must be kept in mind that subclinical neurological abnormalities may be related to Celiac disease, and Celiac disease may be the underlying cause in the patients with overt neurological abnormalities in childhood.